Students’ Problem Solving Skills in Learning Using Physics E-Learning Based on Google Classroom - Devy Indasari; Sutrio Sutrio; Muh. Makhrus (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2022)
This study aims to improve students' problem-solving skills in circular motion material using Google Classroom-based e-learning physics blended learning. The type of research used is (Research & Development) which refers to the 4D model (Define, Design, Develop and Disseminate). The results obtained at the limited trial stage in the form of data on students' problem-solving abilities during learning activities obtained from student worksheets (LKPD) and data on students' problem-solving abilities after participating in learning activities as a whole obtained from the results of pretest and posttest. to 20 students of class X MIPA 2 SMAN 2 Taliwang. The results of the assessment using a Likert scale on students' problem-solving abilities during learning activities have an average percentage of 78.5% with practical criteria. The results of students' problem-solving abilities after participating in learning activities as a whole were analyzed using the N-Gain test and obtained a significant increase in problem solving abilities, namely 61.3% with quite effective criteria. So, it can be concluded that the e-learning based on google classroom which was developed is quite practical and effective to improve students' physics problem solving ability.